Hydrothermal nontronite formation associated with microbes from low‐temperature diffuse hydrothermal vents at the South Mid‐Atlantic Ridge. Issue 9 (13th September 2017) - Ta, Kaiwen; Peng, Xiaotong; Chen, Shun; Xu, Hengchao; Li, Jiwei; Du, Mengran; Hao, Jialong; Lin, Ying
Abstract: Oceanic nontronite deposits have been identified to be closely related to low‐temperature hydrothermal activities. However, their formation mechanisms associated with microbes in diffuse hydrothermal vents still remain largely unknown. The friable deposits, collected from the low‐temperature diffuse flow at the Southern Atlantic Ridge, display a layered structure. Scanning electron microscope and transmission electron microscope analyses reveal that abundant filamentous, spherical, and rod‐shaped mineralized forms are preserved in the yellowish‐green layer of the deposits. These mineralized forms primarily consist of Si and Fe. Selected area electron diffraction patterns of the mineralized forms indicate that they are composed of nontronite. High intensities of 12 C and 12 C 14 N signals derived from cellular structures determined by nanosecondary ion mass spectrometry suggest the intimate relationship between nontronite and microbes. The results of 454 pyrosequencing analyses provide insights into the microbial communities involved in the biologically induced mineralization in the yellowish‐green layer. We propose an evolutionary model for establishing paragenetic sequences among nontronite, Mn oxide, and Fe oxyhydroxide in the deposits. This paragenetic sequence could be widespread in modern and ancient low‐temperature hydrothermal fields. Key Points: The abundant filamentous, spherical, and rod‐shaped mineralized forms are preserved in the yellowish‐green deposits Nontronite formation is linked to the biologically influenced mineralization in the low‐temperature hydrothermal diffuse fluids Paragenetic sequence is controlled by the subtle variation in redox conditions and the evolution of the hydrothermal fluids